2022
DOI: 10.1094/pdis-11-20-2341-re
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Puccinia striiformis f. sp. tritici Races and Virulence in Wheat Growing Regions of Kenya from 1970 to 2014

Abstract: Stripe rust, caused by the fungal pathogen Puccinia striiformis f. sp. tritici (Pst), is a major threat to wheat (Triticum spp.) production worldwide. The objective of this study was to determine the virulence of Pst races prevalent in the main wheat growing regions of Kenya, which includes Mt. Kenya, Eastern Kenya, and the Rift Valley (Central, Southern, and Northern Rift). Fifty Pst isolates collected from 1970 to 1992 and from 2009 to 2014 were virulence phenotyped using stripe rust differential sets, and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…PstS2 was first reported in Europe in 2000 [31], where only a relatively small wheat area was affected due to widespread deployment of PstS2-resistant cultivars [34,35]. Subsequent studies indicated East Africa as putative origin of PstS1/PstS2 [12], first detection of PstS1 dating back to an isolate sampled in Kenya in 1974 [36]. The fact that PstS1 has not been reported in P. striiformis populations outside North America and Australia since 2000 (except few samples in East Africa) may suggest an accidental, human-mediated spread of this strain, rather than random airborne spore movements around the globe between 2000 and 2002.…”
Section: Recent Inter-continental Spread Of Wheat Rust Fungimentioning
confidence: 99%
“…PstS2 was first reported in Europe in 2000 [31], where only a relatively small wheat area was affected due to widespread deployment of PstS2-resistant cultivars [34,35]. Subsequent studies indicated East Africa as putative origin of PstS1/PstS2 [12], first detection of PstS1 dating back to an isolate sampled in Kenya in 1974 [36]. The fact that PstS1 has not been reported in P. striiformis populations outside North America and Australia since 2000 (except few samples in East Africa) may suggest an accidental, human-mediated spread of this strain, rather than random airborne spore movements around the globe between 2000 and 2002.…”
Section: Recent Inter-continental Spread Of Wheat Rust Fungimentioning
confidence: 99%
“…Stripe rust race 134 with virulence for Yr7, 6, 9+ genes were present in Ethiopia, Kenya, Syria, and Yemen [34]. Thirteen races with virulence corresponding to stripe rust resistance genes Yr1, Yr2, Yr3, Yr6, Yr7, Yr8, Yr9, Yr1 7, Yr25, Yr27, and Avocet S are present in wheat-growing regions of Kenya [35], these races belong to either strain Pst1 or Pst2 which might have been present much earlier than 1982 and 1970.…”
Section: Wheat Rust Diseases In Kenyamentioning
confidence: 99%
“…SCAR markers SCAR1265 and SCAR1400 were developed in wheat to identify powdery mildew (B. graminis) gene Pm21, which was located on 6AL/6Vs same locus for gene Yr26 [115]. Species-specific sequencecharacterized-amplified-region (SCAR) markers have been used to characterize stripe rust races in Kenya [35].…”
Section: Use Of Sequence-characterized-amplified Region (Scar)mentioning
confidence: 99%